Nanostructured lipid carriers as a novel tool to deliver sclareol: physicochemical characterisation and evaluation in human cancer cell lines (Brazilian Journal of Pharmaceutical Sciences, 2022)
Sclareol (SC) is arousing great interest due to its cytostatic and cytotoxic activities in several cancer cell lines. However, its hydrophobicity is a limiting factor for its in vivo administration. One way to solve this problem is through nanoencapsulation. Therefore, solid lipid nanoparticles (SLN-SC) and nanostructured lipid carriers (NLC-SC) loaded with SC were produced and compared regarding their physicochemical properties. NLC-SC showed better SC encapsulation than SLN-SC and was chosen to be compared with free SC in human cancer cell lines (MDA-MB-231 and HCT-116). Free SC had slightly higher cytotoxicity than NLC-SC and produced subdiploid DNA content in both cell lines. On the other hand, NLC-SC led to subdiploid content in MDA-MB-231 cells and G2/M checkpoint arrest in HCT-116 cells. These findings suggest that SC encapsulation in NLC is a way to allow the in vivo administration of SC and might alter its biological properties.